2015
DOI: 10.1002/jqs.2788
|View full text |Cite
|
Sign up to set email alerts
|

A diatom–conductivity transfer function for reconstructing past changes in the Southern Hemisphere westerly winds over the Southern Ocean

Abstract: Sub-Antarctic islands are ideally placed to reconstruct past changes in Southern Hemisphere westerly wind behaviour. They lie within their core belt (50-60˚S) and the strong winds deliver sea salt ions to the islands resulting in a west to east conductivity gradient in their water bodies. This means that the stronger (or weaker) the winds, the higher (or lower) the conductivity values measured in the water bodies. A survey of the water chemistry and diatom assemblages of lakes and ponds on sub-Antarctic Campbe… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

2
7
0

Year Published

2015
2015
2023
2023

Publication Types

Select...
7
1

Relationship

2
6

Authors

Journals

citations
Cited by 13 publications
(9 citation statements)
references
References 74 publications
2
7
0
Order By: Relevance
“…Changes in sea salt aerosol deposition were tracked by shifts in sub-fossil diatom species assemblages in the sediments. These respond to changes in lake water conductivity resulting from past sea salt aerosol delivery 39 . A weighted averaging statistical model to reconstruct past conductivity was based on measuring the present relationship between modern diatom species assemblages and lake water conductivity in 64 lakes on the island 40 (see Supplementary Methods).…”
Section: Resultsmentioning
confidence: 99%
“…Changes in sea salt aerosol deposition were tracked by shifts in sub-fossil diatom species assemblages in the sediments. These respond to changes in lake water conductivity resulting from past sea salt aerosol delivery 39 . A weighted averaging statistical model to reconstruct past conductivity was based on measuring the present relationship between modern diatom species assemblages and lake water conductivity in 64 lakes on the island 40 (see Supplementary Methods).…”
Section: Resultsmentioning
confidence: 99%
“…600 km south of New Zealand and 3800 km north of the Antarctic Continent. The island has a total surface area of 113 km 2 , reaching an altitude of 569 m. Saunders et al (2015) provide details on the climate, geomorphology and vegetation of the island.…”
Section: Methodsmentioning
confidence: 99%
“…A cloudy, moist, and cool climate prevails with minimal sunshine (Thorn 2008). The island has a total surface of 113 km 2 and reaches an elevation of 569 m. More details on the climate, geomorphology, and vegetation of the island can be found in Saunders et al (2015).…”
Section: Study Area and Samplingmentioning
confidence: 99%
“…The bryophyte samples were subsequently stored in the British Antarctic Survey Herbarium in Cambridge (UK). More than 40 years later, Saunders et al (2015) assessed the aquatic diatom flora found in lakes and reported important differences with the nearby Macquarie Island diatom assemblages, despite a high floristic similarity between Campbell Island and the sub-Antarctic islands in the southern Indian Ocean ( Van de Vijver et al 2002a) and the diatom flora in the Tasmanian and New Zealand mountain lakes (Vyverman et al 1995;Hodgson et al 1997;Kilroy et al 2007;John 2016a).…”
Section: Introductionmentioning
confidence: 99%